Electrical properties of gamma-modified composites copolymer of polyvinylidene fluoride with tetrafluoroethylene and silicon - Nuruyev, I.M. (Вопросы атомной науки и техники, 2019)
The concentration and temperature dependences of the electrical properties of the composites obtained on the basis of a copolymer of polyvinylidene fluoride with tetrafluoroethylene P(VDF–TFE) with silicon nano- and microparticles were investigated, and the effect of gamma-radiation on them was studied. It is shown that the cause of the change in the concentration and temperature dependences of the electrical properties of irradiated composites P(VDF)–TeFE)/Si, apart from crosslinking and destruction, is the uneven distribution of the energy of the absorbed radiation between the components of the composite material.